Estudo da associação entre Angiostrongylus vasorum com Achatina fulica - Aytube Coaglio Silva Lucas (2017)
Angiostrongylus vasorum is a parasitic nematode of domestic and wild canids, whose adult form can be found in the right ventricle, pulmonary arteries and their ramifications. The cycle involves is heteroxene with the participation of aquatic and terrestrial molluscs as intermediate hosts. The present study evaluated the relationship between Achatina fulica experimentally infected with 1000 L1 of A. vasorum on days 0, 1º, 8º, 13º and 30º after infection (dpi). The presence of phenoloxidase (PO) in the hemolymph acellular fraction in the hemocyte supernatant was analyzed using the L-DOPA, L-Tyrosine and p-phenylenediamine (PPD) substrates, as well as the evidence of melanin in the tissue of the region cephalopodal. The level of nitric oxide in the acellular fraction of A. fulica was quantified by the Griess reaction. In this study, the morphology and morphometry of L1, L2 and L3 were evaluated and fixed with 4% paraformaldehyde and labeled with antibodies: anti-β-tubulin, anti-α-tubulin, anti-collagen 1/1-collagen and anti-β-actin, and by the dyes: picrosirius and oil red, under an epifluorescence microscope. To observe the natural infection by A. vasorum was carried out the chemical digestion of A. fulica captured in the city of Belo Horizonte, Sabará, Igarapé and Lagoa Santa. PO activity and tissue melanin production were observed in A. fulica, varying between control and infected. At the 1st dpi, L-tyrosine (p <0.001), L-DOPA (p <0.05) and PPD (p <0.01) were observed, increased PO coincident with melanin. At 8° dpi, modulation of L-DOPA-dependent PO (p <0.001) and L-Tyrosine, but not with PPD (p <0.05) was observed, while in the tissue analyzes they were inversely proportional to PO on substrates L-DOPA and L-Tyrosine. At 13° dpi the inhibition of PO occurred in all three substrates and circulating levels of melanin in the tissue decreased. At 30° dpi the PO with L-Tyrosine did not change, whereas for L-DOPA and PPD they increased and in the tissue there was a decrease in the concentration of melanin. At the level of NO, it increased up to 8° dpi and decreased to 30° dpi. The larvae L1, L2, L3 of A. vasorum present in the cytokinetic composition fibers of actin, tubulin and collagen. With picrosirus, in the epifluorescence associated with ApoTome obervou internal structures in the anterior and posterior region. In the oil red, lipids were found to be dispersed throughout L1, L2 the lipid reserves fill the entire length of the larva and L3 were located in the posterior part of the larvae. In the molluscs of the metropolitan region of Belo Horizonte, only larvae of the genus Strongyluris sp and Rhaditis sp. were found. The work presents a possible mechanism, phenoloxidase, in the elimination of larvae of A. vasorum, mainly in the L1 to L2 stage, where there is an increase of nitric oxide and melanin in the tissues. Picrossirius was the used dye that presented the best result for morphological analysis of the larvae, having the advantage of being cheap and easy to access. The molluscs collected in Belo Horizonte and in the metropolitan region were not infected with metatrongilid larvae, and could indicate the absence of the parasites in these places, being areas free for metastrongilideos.